FAKTOR FUNDAMENTAL DAN RISIKO SISTEMATIK TERHADAP HARGA SAHAM (Studi pada Perbankan Syariah di Indonesia) - Suryakusuma Kholid H; Yanuar Rachmanysah D.W (JURNAL ILMIAH EDUNOMIKA, 2023)
This study aims to analyze the influence of fundamental factors and systematic risks on sharia stock prices in Islamic banking companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period.In general, there are several indicators in measuring fundamental factors in the financial aspects of each company including NPM, DER, CR, EPS, Beta and Stock Price.Meanwhile, the risk indicator is measured using stock betas. In this study, it will emphasize the results of the assessment on the fundamental financial factors of the company and the level of systematic risk as a benchmark for the level of sharia stock prices in Islamic banking. The object of this study is a Sharia commercial bank listed on the Indonesia Stock Exchange.The need for data obtained from islamic bank financial statements and data analysis obtained from the IDX and publications of each Islamic bank.This study uses objects from all Islamic banks listed on the Indonesia Stock Exchange.Financial information and data are obtained from the annual financial statements of all Islamic banks on the IDX.The results of this study obtained that partially variable NPM has a significant effect on the share price of Islamic banks., DER has a significant effect on the share price of Islamic banks, CR has a significant effect on the share price of Islamic banks, EPS does not have a significant effect on the share price of Islamic banks and Beta shares does not have a significant effect on the share price of Islamic banks. Keywords : Islamic bank financial ratio, systematic risk, stock price